Effect of whole-body cryotherapy on recovery after high-intensity training in elite rowers - Huang, Tao; Dan, Linfei; Wang, Weirui; Ren, Jiarui; Liu, Xin; Li, Jianshe (Frontiers in Physiology, 2024)
Purpose: This study aimed to investigate the effect of whole-body cryotherapy (WBC) on acute recovery after a single high-intensity training day. Methods: Twelve elite professional male rowers from the national aquatic training base. They were randomly divided into a WBC group (n=6) and a control group (CON group, n=6). They performed a high-intensity training program, with a single session immediately followed by WBC (-110 °C, 3min) or recovered naturally for 3 min (CON group). Rowing performance, skin temperature, heart rate, blood pressure, and blood lactate concentrations were recorded before training, immediately, 5 minutes, and 15 minutes after the intervention. Blood samples were collected early in the morning of the day of intervention and that of the following day. Results: 1) the blood lactate concentrations after WBC were significantly lower than pre-training (p<0.05); 2) the maximum power significantly decreased immediately after WBC compared to pre-training (p<0.05); 3) a significant main effect of time was observed for average speed, which significantly decreased after WBC (p<0.05); 4) a significant main effect of time for blood parameters was observed. Specifically, hematocrit, cortisol, and hemoglobin were significantly lower after WBC than pre-intervention, whereas testosterone/cortisol was significantly higher than pre-intervention (p<0.05). Conclusions: The results of this study showed that a single session of WBC had a positive effect on accelerating the elimination of blood lactate after HIT, but did not significantly change rowing performance and physiological parameters. A single session of WBC was not an effective strategy for elite rowers for acute recovery after HIT.